2004
DOI: 10.1111/j.1463-1326.2004.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel formulation of essential oils on glucose– insulin metabolism in diabetic and hypertensive rats: a pilot study

Abstract: Although all the three formulae decreased SBP in ZFRs, one of the formulae was more effective than the others in lowering circulating glucose in the glucose tolerance testing. Accordingly, some essential oils may be added to the long list of natural products that can affect insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…[50] The combination of cinnamon essential oil with cumin, fennel, oregano, and myrtle essential oils has a synergetic effect on the reduction of blood glucose levels as well as enhancing insulin sensitivity in type 2 diabetes in a rat model. [51] In the study of Cheng et al, [23] defatted soy flour enriched with cinnamon extract had a significant effect on improving glucose metabolism in both in vivo and in vitro experimentation.…”
Section: Antitumor and Anticancermentioning
confidence: 99%
“…[50] The combination of cinnamon essential oil with cumin, fennel, oregano, and myrtle essential oils has a synergetic effect on the reduction of blood glucose levels as well as enhancing insulin sensitivity in type 2 diabetes in a rat model. [51] In the study of Cheng et al, [23] defatted soy flour enriched with cinnamon extract had a significant effect on improving glucose metabolism in both in vivo and in vitro experimentation.…”
Section: Antitumor and Anticancermentioning
confidence: 99%
“…Both in vitro and in vivo animal studies have shown that cinnamon is an insulin sensitizer. 2 Several compounds within cinnamon have been identified as possible sources of this sensitization process.…”
Section: Unanswered Questions and Future Researchmentioning
confidence: 99%
“…For example, Allium cepa (garden onion) and Momordica charantia (bitter melon) have hypoglycemic effects (13,17,24) and improved insulin action in rats fed a high-fat diet (17), while the medicinal plant, Galega officialis, led to discovery and synthesis of metformin, the well-known hypoglycemic medication (64). Essential (volatile) oils of herbs and medicinal plants have long been known to have antimicrobial, antifungal, and antioxidant properties (10,60), as well as exerting hypoglycemic effects in animal models of type 1 diabetes (54,55), type 2 diabetes (Zucker fatty rats), and insulin resistance (59). Thus, it appears that essential oils offer therapeutic potential for the treatment of insulin resistance, although their mechanism of action remains unknown.…”
mentioning
confidence: 99%